A Surface‐Confined Proton‐Driven DNA Pump Using a Dynamic 3D DNA Scaffold. Issue 32 (24th May 2016) - Zhu, Dan; Pei, Hao; Yao, Guangbao; Wang, Lihua; Su, Shao; Chao, Jie; Wang, Lianhui; Aldalbahi, Ali; Song, Shiping; Shi, Jiye; Hu, Jun; Fan, Chunhai; et al.
Abstract : A proton‐driven molecular pump is devised using a surface‐confined dynamic 3D DNA scaffold. A dynamic DNA tetrahedral nanostructure is designed by incorporating a pH‐sensitive i‐motif sequence in one edge, which serves as the scaffold to ensure highly ordered orientation and spatial isolation of this nanomachine on the macroscopic gold surface. It is found that the switching ability of this dynamic tetrahedron is fully maintained on the surface. Importantly, this proton‐driven nanomachine can reversibly pump water and ferricynide in response to pH variation in solution.